Educational Technologies: a Prospective Study - Silva, Flavio Santos (2019)
The present study has a methodology a prospective analysis of the educational technologies considering the patents of the World Intellectual Property Organization (WIPO), Instituto Nacional de Propriedade Industrial (INPI) and works in the literature related to the subject. Based on the survey, we defined the main aspects of education in which these technologies are present and their expectation of evolution. This study also analyzes the position of the countries in the use of such technologies, as well as the companies that emerge as major depositors of patents and their temporal evolution. It was discovered that the educational technologies have a strong investment of the countries best placed in international education rankings and that Brazil falls short of what is produced in these countries. Thus, this study resulted in educational programs in progress related to the country's investment in education and as a source of investments that impact on the research of new educational technologies.